The use of two didactic strategies - the environmental action and the poster - in the repertoire of Ecological Problems of the School of General Studies, University of Costa Rica as tools to do environmental education inside and outside the house of studies - Jiménez Morales, Ana Patricia (2018)
This work focuses on the importance of two teaching strategies – the environmental action and the poster – used in the Repertoire of Ecological Problems, such as tools for environmental education. In order to assess the degree of acceptance and relevance of this practice to the course were consulted to 173 students at the end of the 1st semester of 2015. The environmental actions taken involve public primary and secondary schools, as well as government and private protected areas, also the society in general. Students identify real environmental issues and propose solutions through voluntary work, environmental workshops and donations of educational materials, among other things. The activity was widely accepted by the students, and they made very pleasing comments. In addition, they choose an environmental topic and present it to the University and the civil community with a poster during the week of the environment, first week of June. Both activities have a positive impact on the student´s professional training, make them sensitive to the subject of the environment that surrounds them; it educates them on the environment concerns and also allows them to demonstrate part of work that is carried out within the University. Moreover, it also benefits the Planet because; it is expected from them, as future professionals to take more responsible decisions involving with the environment.